Deteksi Odontoglossum ringspot virus pada Anggrek Asli Koleksi Kebun Raya di Indonesia - Mahfut, Mahfut; Daryono, Budi Setiadi; Somowiyarjo, Susamto (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Native orchid is one of Indonesian natural resources which play important role as parental materials in breeding program. Virus infection is one of the limiting factors in the cultivation of orchid. The purpose of this study was to detect Odontoglossum ringspot virus (ORSV) from native orchid. Symptomatic orchids were collected from 5 botanical gardens, i.e. Bogor, Cibodas, Purwodadi, Balikpapan, and Enrekang Botanical Gardens. Detection and identification was conducted by serological method using ORSV specific antisera, followed by RT-PCR and DNA sequencing. The serological test showed that 5 samples gave positive reaction against ORSV antiserum, i.e. Phalaenopsis amboinensis (KRB2) and Phalaenopsis amabilis (KRB12) from Bogor Botanical Garden, Phalaenopsis amabilis (KRP18) and Dendrobium salacence (KRP20) from Purwodadi Botanical Garden, dan Phalaenopsis modesta J. J. Sm. (KRBp5) from Balikpapan Botanical Garden. RT-PCR of the 5 samples using specific primer of ORSV coat protein gene was successfully amplified fragment DNA with size ± 474 bp. Homology analysis of those 5 ORSV isolates showed the highest index similiarity of 99.8% with corresponding sequences from 14 other ORSV isolates. Phylogenetic analysis indicated that ORSV KRB2 and KRP18 isolates was clustered in a separate group far from ORSV isolates in other countries. This is the first report of ORSV infection on native orchids collection from 5 botanical gardens in Indonesia.